Complexity and the Arrow of Time / [electronic resource] - Lineweaver, Charles H.; Davies, Paul C. W.; Ruse, Michael (Cambridge : Cambridge University Press, 2013)
There is a widespread assumption that the universe in general, and life in particular, is 'getting more complex with time'. This book brings together a wide range of experts in science, philosophy and theology and unveils their joint effort in exploring this idea. They confront essential problems behind the theory of complexity and the role of life within it: what is complexity? When does it increase, and why? Is the universe evolving towards states of ever greater complexity and diversity? If so, what is the source of this universal enrichment? This book addresses those difficult questions, and offers a unique cross-disciplinary perspective on some of the most profound issues at the heart of science and philosophy. Readers will gain insights in complexity that reach deep into key areas of physics, biology, complexity science, philosophy and religion.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Complexity (Philosophy)